1998
DOI: 10.1002/(sici)1521-3951(199811)210:1<199::aid-pssb199>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The Moment Sum Rule and Its Consequences for Ferromagnetism in the Hubbard Model

Abstract: The sum rule for the moments of the spectral density is discussed for the single-band Hubbard model. It is shown that respecting the sum rule up to the order m 3 is conceptually important for a qualitatively correct description of the quasi-particle band structure in the strong-correlation regime. Different analytical approximations for the self-energy are analyzed with respect to their compatibility with the moment sum rule. To estimate the practical usefulness of the sum rule, correlation functions and dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(126 citation statements)
references
References 91 publications
(266 reference statements)
9
116
0
1
Order By: Relevance
“…One observes a reduction of the ferromagnetic region compared to the SDA result. So, similar to the Hubbard model [30,49], quasiparticle damping is unfavourable for ferromagnetism. However, apart from the lower critical n (tot) , the MAA and SDA curves are very similar.…”
Section: Resultsmentioning
confidence: 99%
“…One observes a reduction of the ferromagnetic region compared to the SDA result. So, similar to the Hubbard model [30,49], quasiparticle damping is unfavourable for ferromagnetism. However, apart from the lower critical n (tot) , the MAA and SDA curves are very similar.…”
Section: Resultsmentioning
confidence: 99%
“…This is, however, the interesting case concerning band-ferromagnetism. For the single-band model in the limit of infinite spatial dimensions the theories are thoroughly tested against numerical exact results available in this limit 23 . It is found that the SDA as well as the MAA systematically overestimate magnetic quantities such as the Curie temperature but turn out to give a qualitative satisfying description of band-ferromagnetism 23 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Terms of the R 14 (1)↑ (ω) and R 14 (2)↑ (ω) type are taken into consideration in different ways in various approximations. For example, in Hubbard-III approximation only the first of them is included [5,9]. In this work we use the alloy analogy approximation; in this case terms (64, 65) are neglected (see [9]).…”
Section: Discussionmentioning
confidence: 99%